The New Messiah : His Holiness Janmasiddha Thakur Sri Sri Balak Brahmachari : a collection of some selected events and sayings from the divine life of Janmasiddha (inborn) Thakur Sri Sri Balak Brahmachari - Rāẏadā (R.N.R. Publishers, 1979)
On the life and teachings of Bālaka Brahmacārī, b. 1920, Hindu religious leader.